Waterfall mechanism and three-stage implementation model for interconnected dangerous goods warehouse operations. Issue 9 (1st September 2020) - Zhang, Fangwei; Liew, Guan ke; Zhang, Ziyu; Lin, Zhihao; Sun, Jing; Li, Jiaru; Tang, Xufeng
Abstract : In elevating the efficiency and practicality of warehouse operations, our team proposes the concept of interconnected dangerous goods warehouses. To support the operations of this kind of warehouse, this original study addresses three factors that affect the operations of such warehouses, namely the distance traveled by the forklift (cost factors), the similarity between the distances operated by the forklifts (efficiency factors), and the distance between each stack of goods in the warehouse (safety factors). In considering safety factors and improving the operational efficiency of stocking in or out of dangerous goods, this study proposes a waterfall mechanism for warehouse operations. The main characteristic of this study is a three-stage model to integrate key factors influencing the operations of dangerous goods stocking in or out warehouse. Thereafter, an example is given to verify the effectiveness and feasibility of the proposed waterfall mechanism and the three-stage model.